Effect of tree species and soil texture on the carbon stock, macronutrient content, and physicochemical properties of regenerated postfire forest soils. (3rd October 2021) - Woś, Bartłomiej; Józefowska, Agnieszka; Likus‐Cieślik, Justyna; Chodak, Marcin; Pietrzykowski, Marcin
Abstract: Many countries are having increased frequency and severity of wildfires, including mega‐fires. The revegetation of postfire sites and tree species selection are the most important counteracting measures. In this study, we analyzed the effect of tree species (Scots pine, European larch, common birch) on the C stock, macronutrient content, and physicochemical parameters (pH, sorption complex properties) of regenerated soil of different textures (sands and loams) in a large, postfire site. Nearly, 30 years after the fire, soils differed among the species. The carbon stock under larch was higher in litter (Oi + Oe) horizons than under birch. In mineral horizons (0–5 cm), the C stock was highest under birch. Litter layers under birch had a higher pH, a lower C:N ratio, and higher N, P, Ca, and Mg content compared to layers under pine and larch. In the A‐horizons (0–5 cm), soils under birch was higher in soil organic carbon (SOC), cation exchange capacity (CEC), and acidity than soils under conifers. Soil texture in the studied range—from sands to loams—had only a limited effect on the properties of the studied postfire soils. Thus, our results indicate that the tree species used for the reforestation of postfire sites are crucial to the properties of regenerating soils and restoring the ecological functions of soils. Among the studied tree species, common birch had the most pronounced effect on soil properties, and this is especially significant because the species has appeared by spontaneous succession.